The mediating effect of privacy concern on intention to use self-service technology in hotel / Azlinda Hakim Lokman Hakim and Hairunnisa Mohamad Ibrahim - Lokman Hakim, Azlinda Hakim; Mohamad Ibrahim, Hairunnisa (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2023)
Self-service technology (SST) is an innovation that requires communication over the internet. In the hotel business, it has become more widespread as customers' interactions with workers and technology have changed. SST are increasingly valued by customers for their convenience, consistency and control. SST help hotels to improve service standards and technological applications available allows hotel to choose the application that best matches the guest and the hotel's needs. Despite their increasing popularity, some might have doubt about using the technology as this may involve confidentiality and privacy details. The study proposes a research framework to suggest the direct relationship and moderating roles of privacy towards SST. Data collected from customer with SST experiences are examined through PLS-SEM and hierarchical moderated regression analysis. Results indicate that customer privacy enhance perceived usefulness and perceived ease of use towards intention to use SST.